(3hUGjG Gdedhc hCHfGA Gdedhc ef bMWGf Hf ghO GdfHi Ydjg GdSdGes
(3ChdgG (B:s
(3CLeYJ GdYdeGA Ydi Cf Chd fHi HYKg Gddg ef HYO GdfHi fhM Ydjg GdSdGe HTjQkG hfPjQkG hGFJefg Ydi hMjg hQSGdJg ghO GdfHi Udi Gddg Ydjg hSde s
(3BNQgG (B:s
(3hBNQg ef bUjOI ddMGQK Hf cYH jNGWH Hfjg (B: (3hdGJHOChG HGdMQH ef de jcf dce ef GdfGS HGdYOhGf hGdXde HGOjG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3GdfSNI ai KdGKI CLRGAs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdSjGSI hGdGLJeGYs